Efficient Routing in VANETs using Traffic Awareness (International Journal of Engineering and Computer Science, 2014)
The basic idea in VANETs is to have an adhoc connection between close by vehicles. The routing in vehicular networks is exposed to danger by the harmful nodes which aim to endanger the delivery of messages. Compromised nodes can extremely impact the performance of the network by capitalizing a number of attacks. To minimize these problems, a way of securing beacon-less routing algorithm for vehicular environments (S-BRAVE) against selective forwarding attacks using neighbouring nodes as guard nodes is developed. They watch for the message to be sent by the next forwarder, in case this vehicle does not forward the message, they take the responsibility of sending the message to the next hop. To increase the packet delivery ratio S-BRAVE routing algorithm is extended by including the traffic awareness of the roads, thereby routing the packets in a denser environment gives higher probability of delivering the packets to their respective destinations.